Transgressive phenotypes and evidence of weak postzygotic isolation in F1 hybrids between closely related capuchino seedeaters. - Leonardo Campagna; Pablo Rodriguez; José Carlos Mazzulla (PLoS ONE)
Postzygotic reproductive isolation may become strong only once the process of speciation is in its advanced stages. For taxa in the early stages of speciation, prezygotic reproductive isolation barriers may play a predominant role in maintaining species boundaries. Here, we study the recent capuchino seedeater biological radiation, a group of highly sympatric species from the genus Sporophila that have diversified during the Pleistocene in Neotropical grasslands. Capuchinos can be diagnosed by adult male coloration patterns and song, two sets of characters known to contribute to pre-mating reproductive isolation. However, it remains unknown whether potzygotic incompatibilities contribute to maintaining species limits in this group. Here we use existing breeding records from captive individuals to test for patterns consistent with F1 inviability. We compare hatching success, fledging success, and the sex ratio at adulthood between conspecific and hybrid capuchino pairs. We observed a trend towards lower numbers of the heterogametic sex among adult hybrids, consistent Haldane's rule, but this was supported by only one of our statistical tests. Our study is the first to document hybrid male capuchino phenotypes based on known crosses. We observed phenotypes that were similar or intermediate to those of the parental species, as well as novel plumage patterns that have not been described in the wild. One cross produced a plumage pattern that has been observed at low frequencies in natural populations. We discuss the implications of our results for understanding the relative importance of the mechanisms of reproductive isolation in capuchino seedeaters.